Survey of Knowledge, Attittudes and Practices about Antibiotic Use in Colombian Physicians - Jorge Cortes (Asociación Colombiana de Infectología, 2018)
We applied a voluntary survey about knowledge, attittudes and practices about antibiotic prescription at three scientific meetings of the Asociacion Colombiana de Infectología, on February 2008. The survey was anonimous and individual. The results were analyzed using Excel 2007 and STATA 2000. We analyzed 96 surveys, 29 from general practitioners and 67 medical specialists. Physicians had wrong knowledge about antibiotic use between 29,2% and 67,42%. Most physicians (97.4%) considered the antibiotics have to be sold only under medical prescription. Many physicians recognized having limited knowledge about antibiotic dosing interval and security. 60% physicians disagreed with the application of guidelines from other countries in our enviroment and 76% physician consider the infectious disease experts contribute to clinical management of patients. Physicians reported having support from an infectious disease expert on 72%, and had strategies to restrict the use of some antibiotics, likecontact isolation when multi-resistant organisms had been suspected. There were not differences between answers according to years of experience. Several physcians reported conservative practices and rational antibiotic use with limited knowledge about antibiotic pharmacokinetics and pharmacodynamics.